Socio demographic pattern, health problems and social behaviors of adolescents attending Teaching Hospital, Batticaloa, Sri Lanka - Arulpragasam, A. N.; Kisokanth, G.; Randeny, R. A. N. S.; Fernando, A. D. (My University, 2019)
Adolescent period is one of rapid growth and development where many changes occur physically, socially and emotionally. Unhealthy behaviour patterns begun and established during adolescence commonly link to several illnesses. The study was aimed to assess the socio-demographic pattern, health problems, social behaviors and the satisfaction towards the existing health care facilities in the adolescent age group. A cross-sectional descriptive study was conducted among 170 adolescents (10-19 years) attending Teaching Hospital, Batticaloa during the study period. Adolescents admitted or attending all paediatric and surgical wards were recruited in an all-inclusive, consecutive basis. A pre-tested inter-viewer administered questionnaire was utilized to collect data. Most (60%) of them were in the 10-14 year age group with a mean age of 13.6 (SD±2.52) years. Nearly 9% were overweight and the mean body mass index was 19.83 (SD±4.46) kg/m2. Fourteen percent had been admitted due to road traffic accidents which was high among 15-18 year age group (p>0.05). Signifi-cantly lower percentage of females (48%) compared to males (80%) had engaged in regular physical activity (p=0.00). A significantly higher percentage of female adolescents (2.4%) experienced suicidal thoughts at least once due to stress/depression (p=0.00). Majority of the adolescents reported better satisfaction on the expected care from health care professionals at the hospital and were highly satisfied with existing ward facilities and other health facilities. A significantly higher percentage of female adolescents experienced suicidal thoughts due to stress/depression and lower percentage of female adolescents engaged in regular physical activity. Majority of adolescents were highly satisfied with existing ward facilities and other health facilities.
Keywords: adolescents; health problems; social behaviours; socio-demographic pattern; Batticaloa